THE EFFECT OF BULLYING ON INCREASING THE INCIDENCE OF SELF-HARM AMONG ADOLESCENTS IN INDONESIA: A SCOPING REVIEW - Ryka Widyaningtyas; Meidiana Dwidiyanti (Medical Studies and Health Journal (SEHAT), 2025)
Bullying is a widespread issue that significantly affects the mental health of adolescents, particularly in Indonesia. The link between bullying and self-harm behaviors among adolescents has raised concerns, yet a comprehensive understanding of this relationship in the Indonesian context is lacking. To explore the effect of bullying on increasing the incidence of self-harm among adolescents in Indonesia, mapping existing literature and identifying research gaps. A scoping review was conducted following the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. Studies were identified from the database Scopus using the PCC (Population, Concept, Context) framework. The review focused on studies examining the relationship between bullying (physical, verbal, and cyberbullying) and self-harm among adolescents aged 12-18 in Indonesia. The studies included were (n= 6) from 93 publications with search terms. The findings reveal that bullying is a significant factor contributing to increased self-harm behaviors among Indonesian adolescents. Various forms of bullying, including physical, verbal, and cyberbullying, were consistently linked to emotional distress, depression, and self-harm. The lack of adequate social and familial support further exacerbates these behaviors. However, research specifically focusing on cultural factors and long-term effects of bullying on self-harm in Indonesia remains sparse. Bullying plays a critical role in increasing the incidence of self-harm among Indonesian adolescents. This review highlights the need for more in-depth studies on the socio-cultural context of bullying in Indonesia and the development of preventive strategies and mental health interventions to mitigate its impact.